Cumulative risk factors for adolescent depressive symptoms: findings from a Taiwanese school-based sample. Issue 3 (1st September 2020) - Huang, Yu-Te; Yen, Cheng-Fang
ABSTRACT: This cross-sectional study investigated the cumulative effect of risk factors for depressive symptoms. The primary hypothesis was that an increase in the risk factor exposure is associated with the odds of adolescent depression. A multi-stage cluster sampling method was administered to recruit participants. 1, 306 Taiwanese high school students aged 15 to 18 completed self-report questionnaires to report their levels of individual risk factor and depressive symptoms. Risk factors under investigation included low self-esteem, family economic constrain, parent-adolescent conflict, negative peer relationship and academic expectation stress. All risk factors significantly predict adolescents' risk for developing depression. A graded dose-response relationship was observed, meaning the odds of having depression rose along with an increase in the cumulative risk index. The findings yield support for the individual and cumulative effects of these salient risk factor on adolescent depression. The cumulative risk index can provide a useful instrument for depression screening and intervention.